Comparative Analysis of Steel Structure with Rigid and Semi Rigid Joints Using Analysis Tool ETABS A Review - Chandrakanta Patel; Shiva Verma; Lokesh Singh (International Journal of Scientific Research in Civil Engineering, 2022)
Generally, in steel structure the connection between beam and column are designed as moment connection and pinned connection, but in actual condition the structure behaves between these two conditions, resulted into semi-rigid condition which is intermediate stage between rigid and pinned joints. Effect of semi-rigid connection on multi-story multi-bay frame is accomplished in this paper. In this paper literature survey is presented related to analysis of steel structure.
Keywords: Multi-story Multi-bay Frame; Semi-rigid Connections; Fixity Factor; Brace Frame; Rigid Connections